We want to find the solutions for the following equation:
![x^3+8x^2+4x-48=0](https://img.qammunity.org/2023/formulas/mathematics/college/zyaqcg2i4g949t1giuqdr4rxlglboj8s4d.png)
Since (x + 4) is a factor, we can rewrite this equation as a product of this factor by a second degree equation.
![\begin{gathered} x^3+8x^2+4x-48=(x+4)(ax^2+bx+c) \\ x^3+8x^2+4x-48=ax^3+bx^2+cx+4ax^2+4bx+4c \\ x^3+8x^2+4x-48=ax^3+(4a+b)x^2+(c+4b)x+4c \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/aghd9s6x9yux8wny40gofaar3lmqu756b4.png)
Comparing the coefficients from the left side with the coefficients from the right side, we get the following equations:
![\begin{gathered} a=1 \\ 4a+b=8 \\ c+4b=4 \\ 4c=-48 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/imrmq1g5kgivxw3x15cqyb9kfe6sfsa60k.png)
Solving this system, we get the following results:
![\begin{gathered} a=1 \\ b=4 \\ c=-12 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/n2jxhkl45204s8s2n2mzp0g07py2691hoz.png)
Rewriting our polynomial, we have
![x^3+8x^2+4x-48=(x+4)(x^2+4x-12)](https://img.qammunity.org/2023/formulas/mathematics/college/emhty5fg82jwhwcpfam9xi9dcstzglg69r.png)
We can rewrite our original equation as
![(x+4)(x^2+4x-12)=0](https://img.qammunity.org/2023/formulas/mathematics/college/2zm67hwig20836mion2rwku7b5o4a47per.png)
We have a product of two terms, then, if one is zero the product is zero.
To find the roots of this polynomial, we have to solve them individually
![\begin{cases}x+4=0 \\ x^2+4x-12=0\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/gb0s7jtkkdakml1at52ebimi4606fi7f87.png)
The solution for the first equation and the first root, is x = -4. Solving the second one we get the two remaining roots. We could solve it using the Bhaskara Formula, but I'm going to factorize it again using the same process.
![\begin{gathered} x^2+4x-12=(x+k)(x+l) \\ x^2+4x-12=x^2+(k+l)x+kl \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yfi9uncqaz18be87qbbbq1ktakdxlvgsrp.png)
![\begin{cases}k+l=4 \\ kl=-12\end{cases}\Rightarrow\begin{cases}k=-2 \\ l=6\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/zztgun1agptv1vc3zbokc8ybkgdgrmfcde.png)
Our second degree polynomial can be rewritten as
![x^2+4x-12=(x-2)(x+6)](https://img.qammunity.org/2023/formulas/mathematics/college/z9sd06t779ypkp7hga10obm9p8jkya19ob.png)
This means our other roots are x = 2 and x = -6.
![\begin{gathered} x_1=-4 \\ x_2=2 \\ x_3=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/87j43ephojapbw6amym8d6cr42owyh76n7.png)